2019
DOI: 10.1038/s41385-018-0108-2
|View full text |Cite
|
Sign up to set email alerts
|

Batf2 differentially regulates tissue immunopathology in Type 1 and Type 2 diseases

Abstract: Basic leucine zipper transcription factor 2 (Batf2) activation is detrimental in Type 1-controlled infectious diseases, demonstrated during infection with Mycobacterium tuberculosis (Mtb) and Listeria monocytogenes Lm. In Batf2-deficient mice (Batf2 −/−), infected with Mtb or Lm, mice survived and displayed reduced tissue pathology compared to infected control mice. Indeed, pulmonary inflammatory macrophage recruitment, pro-inflammatory cytokines and immune effectors were also decreased during tuberculosis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…We previously demonstrated that Batf2 was expressed in CD11b + F4/80 + macrophages (Mϕs) in the spleen, but not adaptive lymphoid cells, and that it contributed to the suppression of immunopathological T h 17 responses during T. cruzi infection (37). A recent study clearly demonstrated that Batf2 expression induced in Mϕs in the lung during infection with M. tuberculosis and Listeria monocytogenes was associated with the pathogenesis of type 1 infectious diseases (43). In addition, this study showed that BATF2 contributed to prevention of type 2 infectious disease caused by Schistosoma mansoni infection in the small intestine.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that Batf2 was expressed in CD11b + F4/80 + macrophages (Mϕs) in the spleen, but not adaptive lymphoid cells, and that it contributed to the suppression of immunopathological T h 17 responses during T. cruzi infection (37). A recent study clearly demonstrated that Batf2 expression induced in Mϕs in the lung during infection with M. tuberculosis and Listeria monocytogenes was associated with the pathogenesis of type 1 infectious diseases (43). In addition, this study showed that BATF2 contributed to prevention of type 2 infectious disease caused by Schistosoma mansoni infection in the small intestine.…”
Section: Resultsmentioning
confidence: 99%
“…BATF2 is predominantly expressed in monocytes and macrophages and has a central role in macrophage activation by regulating inflammatory responses during mycobacterial infection. In human tuberculosis (TB), BAFT2 has been suggested as a biomarker and a potential host directed drug target 31,32 . The CXCL10 chemokine, also known as IFN-γ inducible protein-10 ( IP-10 ), is chemotactic for monocytes and T-lymphocytes by binding to CXCR3 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Genes in the 16-gene ACS signature that mediate detrimental effects during infection of mice-Of the 16-gene ACS signature genes analyzed for functional relevance in mice, we identified three genes (Batf2, Fcgr1, and Scarf1) which contribute to Mtb susceptibility at distinct phases of infection. BATF2 is a basic leucine zipper transcription factor that is closely related to BATF and BATF3 (46), which together regulate dendritic cell differentiation and development. Batf2/3 −/− mice were more resistant to Mtb infection and unexpectedly showed improved Mtb control upon infection during the transition from acute to chronic stages at 60 and 100 dpi (Fig.…”
Section: Delineating the Functional Relevance Of Genes In The 16-genementioning
confidence: 99%